2016
DOI: 10.2215/cjn.10991015
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Urine Output among Patients Treated with More Intensive Versus Less Intensive RRT: Results from the Acute Renal Failure Trial Network Study

Abstract: Background and objectives Intensive RRT may have adverse effects that account for the absence of benefit observed in randomized trials of more intensive versus less intensive RRT. We wished to determine the association of more intensive RRT with changes in urine output as a marker of worsening residual renal function in critically ill patients with severe AKI.Design, setting, participants, & measurements The Acute Renal Failure Trial Network Study (n=1124) was a multicenter trial that randomized critically ill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
34
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 36 publications
1
34
0
1
Order By: Relevance
“…In fact, even in the ATN Study, urine output of .30 ml/h (720 ml/d) was one of the clinical criteria used to identify patients who might have renal recovery; these patients subsequently underwent a timed creatinine clearance to assess renal function (15). However, in this subgroup analysis of the ATN Study by McCausland et al (17), there were no reported differences in rates of dialysis dependence and presumably, no difference in time to renal recovery (although these data were not shown). Thus, it is not clear that the lower urine output observed here associates with less residual renal function.…”
mentioning
confidence: 56%
See 4 more Smart Citations
“…In fact, even in the ATN Study, urine output of .30 ml/h (720 ml/d) was one of the clinical criteria used to identify patients who might have renal recovery; these patients subsequently underwent a timed creatinine clearance to assess renal function (15). However, in this subgroup analysis of the ATN Study by McCausland et al (17), there were no reported differences in rates of dialysis dependence and presumably, no difference in time to renal recovery (although these data were not shown). Thus, it is not clear that the lower urine output observed here associates with less residual renal function.…”
mentioning
confidence: 56%
“…Although this is a well executed study, we believe that some caution needs to be applied to the statement that the findings of this study are "consistent with a potentially early adverse effect of more intensive RRT on residual renal function" (17). There is no doubt that urine output is lower in those receiving more intensive RRT, and there is no doubt that clinicians often use urine output as a surrogate for early renal recovery.…”
mentioning
confidence: 68%
See 3 more Smart Citations